Lignocellulosic nanomaterials production from wheat straw via peracetic acid pretreatment and their application in plastic composites. (1st November 2022) - Pascoli, Danielle U.; Dichiara, Anthony; Roumeli, Eleftheria; Gustafson, Rick; Bura, Renata
Abstract: Cellulose nanofibrils are typically prepared from high-purity bleached pulp through harsh chemical treatments (e.g., TEMPO oxidation), resulting in high costs and environmental impact. In this work, we utilize inexpensive wheat straw feedstock and alkaline peroxide pulping followed by mild peracetic acid (PAA) pretreatment to produce lignocellulosic nanomaterials (nano and microfibrils) with potential bioplastics applications. PAA was chosen due to its biodegradability, non-toxicity, and high reaction selectivity. As-synthesized lignocellulosic nanomaterials were thoroughly characterized and compared to nanofibrils produced via TEMPO oxidation pretreatment and then applied as reinforcing agents in plastic composites. A remarkable case of simultaneous strengthening and toughening of the polymer nanocomposite was achieved with high specific tensile strength (up to 59.5 MPa g −1 cm 3 ), elastic modulus (up to 2.6 GPa g −1 cm 3 ), and fracture strain (up to 138 %). This work is a comprehensive investigation of all process steps involved in lignocellulosic nanomaterials production, from original residue feedstock to final product application. Graphical abstract: Unlabelled Image